Perancangan Aplikasi Website Pembelajaran Daring untuk Peningkatan Kompetensi Karyawan Nusa Computer Menggunakan Python Flask dan MongoDB - Desmon, Johanes; Ayumi, Vina (JSAI (Journal Scientific and Applied Informatics), 2024)
This study aims to develop and implement a web-based e-learning application specifically designed to meet the internal training needs of Nusa Computer. The application was designed using the waterfall methodology, which consists of requirement analysis, system design, implementation, integration, and testing stages. The requirements analysis process was conducted through surveys using Google Forms distributed to Nusa Computer employees to identify training needs and challenges. The application's backend was built using Python Flask, while the frontend was designed with HTML5, CSS3, and JavaScript. MongoDB was used as the database to store user information and learning materials in a structured document format. The interface prototype was designed using Figma, while UML diagrams, such as use case diagrams and class diagrams, were created using draw.io to map user interaction flows and data structures. Based on the analysis results, the developed application includes key features such as learning material management, discussion forums, a vocabulary dictionary, and a dedicated page for discussions with mentors.